Advanced stress-strain model for FRP-confined concrete in square columns. (15th September 2020) - Lin, Guan; Teng, J.G.
Abstract: Extensive research has been conducted on the behavior of fiber reinforced polymer (FRP)-confined concrete in both circular and rectangular concrete columns. In the former columns, the stress-strain behavior of FRP-confined concrete is now well understood and can be closely predicted, but the same cannot be said about rectangular columns. This paper presents a new attempt at understanding and modeling the confinement mechanism in square columns as a special case of rectangular columns, leading to a new stress-strain model. The salient features of the new model include a more rigorous definition of the effective confinement area and a corner hoop strain-axial strain relationship based on advanced finite element results as well as a more reliable definition of the ultimate condition. The proposed model is analogous in approach to analysis-oriented stress-strain models for FRP-confined concrete in circular columns and represents a more advanced and robust method for modeling the stress-strain behavior of FRP-confined concrete in square columns than the existing empirically-based stress-strain models. The approach is also easily extendable to FRP-confined concrete in rectangular columns. The proposed model is shown to be accurate and perform better than the existing stress-strain models of the same type in predicting existing test results.